Targeting Epsins to Inhibit Fibroblast Growth Factor Signaling While Potentiating Transforming Growth Factor-β Signaling Constrains Endothelial-to-Mesenchymal Transition in Atherosclerosis. Issue 8 (2nd January 2023) - Dong, Yunzhou; Wang, Beibei; Du, Mulong; Zhu, Bo; Cui, Kui; Li, Kathryn; Yuan, Ke; Cowan, Douglas B.; Bhattacharjee, Sudarshan; Wong, Scott; Shi, Jinjun; Wang, Da-Zhi; et al.
Abstract : Background: Epsin endocytic adaptor proteins are implicated in the progression of atherosclerosis; however, the underlying molecular mechanisms have not yet been fully defined. In this study, we determined how epsins enhance endothelial-to-mesenchymal transition (EndoMT) in atherosclerosis and assessed the efficacy of a therapeutic peptide in a preclinical model of this disease. Methods: Using single-cell RNA sequencing combined with molecular, cellular, and biochemical analyses, we investigated the role of epsins in stimulating EndoMT using knockout in Apoe −/− and lineage tracing/proprotein convertase subtilisin/kexin type 9 serine protease mutant viral-induced atherosclerotic mouse models. The therapeutic efficacy of a synthetic peptide targeting atherosclerotic plaques was then assessed in Apoe −/− mice. Results: Single-cell RNA sequencing and lineage tracing revealed that epsins 1 and 2 promote EndoMT and that the loss of endothelial epsins inhibits EndoMT marker expression and transforming growth factor-β signaling in vitro and in atherosclerotic mice, which is associated with smaller lesions in the Apoe −/− mouse model. Mechanistically, the loss of endothelial cell epsins results in increased fibroblast growth factor receptor-1 expression, which inhibits transforming growth factor-β signaling and EndoMT. Epsins directly bind ubiquitinated fibroblast growth factor receptor-1 through their ubiquitin-interacting motif, which results in endocytosis and degradation of this receptor complex. Consequently, administration of a synthetic ubiquitin-interacting motif–containing peptide atheroma ubiquitin-interacting motif peptide inhibitor significantly attenuates EndoMT and progression of atherosclerosis. Conclusions: We conclude that epsins potentiate EndoMT during atherogenesis by increasing transforming growth factor-β signaling through fibroblast growth factor receptor-1 internalization and degradation. Inhibition of EndoMT by reducing epsin–fibroblast growth factor receptor-1 interaction with a therapeutic peptide may represent a novel treatment strategy for atherosclerosis.